Dimensi Kompetensi dan Produktivitas Tenaga Pendidik dalam Pelaksanaan Tridharma Perguruan Tinggi - Subakri (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2022)
Abstract Lecturer management must have the main target, namely increasing the quality of their productivity through increasing work efficiency as educators or teaching staff. This article discusses the dimensions of lecturer competency development. The results of the study conclude that at least seven competency areas and their development strategies can be formulated through certain programs that support the improvement of these competency areas. pedagogical competence, information engineering competence, administrative competence, curriculum competence, evaluation competence, and scientific competence (research, publication, and community service). Keywords; Competencies, educators, universities.